2017
DOI: 10.1002/ps.4775
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of a putative biocontrol agent into a range of phytoplasma‐ and liberibacter‐susceptible crop plants

Abstract: DLB is a potential biocontrol agent and its broad spectrum of host plants indicates the possibility of its future use against a range of diseases caused by phloem-limited bacteria. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…For instance, they have been proposed as probiotics for honeybees to sustain insect health against specific pathogens ( Crotti et al, 2013 ; Daisley et al, 2019 ) or as beneficial strains to improve the fitness of sterile male insects vs. conventional ones ( Ben Ami et al, 2010 ; Augustinos et al, 2015 ). Recently, insect symbionts have been suggested as biocontrol agents against phloem-limited pathogens ( Iasur-Kruh et al, 2016 , 2018 ; Gonella et al, 2018 , 2019 ; Lidor et al, 2018 ). In this work, we focused on the bacterial gut inhabitants of the BSF larvae fed on a nutritionally complete diet, on which BSF performance and fitness were previously showed to be higher than on nutritionally poor diets ( Jucker et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, they have been proposed as probiotics for honeybees to sustain insect health against specific pathogens ( Crotti et al, 2013 ; Daisley et al, 2019 ) or as beneficial strains to improve the fitness of sterile male insects vs. conventional ones ( Ben Ami et al, 2010 ; Augustinos et al, 2015 ). Recently, insect symbionts have been suggested as biocontrol agents against phloem-limited pathogens ( Iasur-Kruh et al, 2016 , 2018 ; Gonella et al, 2018 , 2019 ; Lidor et al, 2018 ). In this work, we focused on the bacterial gut inhabitants of the BSF larvae fed on a nutritionally complete diet, on which BSF performance and fitness were previously showed to be higher than on nutritionally poor diets ( Jucker et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Once endophytes enter into the plant, they move systemically (Nigris et al, 2018), spreading in different tissues as shown in Figure 2 , where green fluorescent protein (GFP)-tagged Bacillus licheniformis can be visualized within the stem of a grapevine-inoculated plant. Indeed, endophytes can colonize other tissues and organs, including reproductive organs, thus allowing their transfer through the vascular system (Lidor et al, 2018) or apoplastic spaces (Compant et al, 2011). An analysis of different aerial portions of grapevines was carried out and revealed differential colonization by endophytes; both Pseudomonas and Bacillus were found within the flower and ovules, while only the latter was present in the berries and seeds (Compant et al, 2011).…”
Section: Biodiversitymentioning
confidence: 99%
“…In conclusion, phloem-limited plant pathogenic bacteria such as Phytoplasma, Spiroplasma, and Liberibacter pose a major threat to a list of agricultural crops [12].…”
Section: The Effect Of Qc and Hmf On Phytoplasma In Periwinklementioning
confidence: 99%
“…However, unlike phytoplasma that inhabits the insect midgut, hemocoel, and salivary glands, F. defendens was found only in the insect gut, suggesting that it was not vertically transmitted, but rather acquired from the plant [11]. Indeed, upon foliage application, F. defendens was shown to penetrate the leaf surface and inhabit the vascular tissues of various plant crops including grapevine, orange, pomelo, cotton, cucumber, and carrot, with no apparent phytotoxic effect [12]. Further research showed that a supernatant of F. defendens culture inhibits the culture growth of Spiroplasma melliferum (Entomoplasmatales, Spiroplasmataceae), which is a cultivable model of phytopathogenic Mollicutes [9]; the secretion of metabolites, which directly inhibit phytoplasma growth, was suggested as one possible mechanism by which F. defendens may reduce yellows symptoms.…”
Section: Introductionmentioning
confidence: 99%